Peperomia crypticola C. DC. (Piperaceae): rediscovery and emended description of a rare species of Southeastern Brazil - Marcusso, Gabriel Mendes [UNESP]; Ribeiro, Henrique Lauand [UNESP]; Lombardi, Julio Antonio [UNESP] (Wiley, 2020)
Based on a recent collection, we present the rediscovery of Peperomia crypticola C. DC., a rare species only known from eastern Minas Gerais, Southeastern Brazil. This species was now found in western Rio de Janeiro, more than 200 km apart and more than hundred years after the original description. An emended description, distribution map, color photographs of the fresh collection and comparison of the species with the closely related Peperomia lanceolatopeltata C. DC. are presented.
Keywords: Atlantic Forest; Brazil; Minas Gerais; Piperales; Rio de Janeiro; Serra da Mantiqueira